Implementasi Model Beyond Center and Circle Time (BCCT) Dalam Pembelajaran Berhitung Permulaan Di PAUD Terpadu Biruni Sungailiat Kabupaten Bangka - Sumar Sumar (Sustainable, 2021)
BCCT is a learning model based on a center through a play while learning approach. This study aims to determine the pattern of BCCT, its implementation and factors that influence the implementation process. This research is a qualitative research. The data collection used are observation, interviews and documentation. Data analisyis was carried out through 3 stages, namely reducing data or sorting out data that is considered important and discarding data that is not needed, then presenting the data that has been selected so that conclusion can be drawn. The results showed that: the BCCT pattern used in the blueni integrated PAUD is almost in accordance with that set by the ministry of national education, while the process of implementing BCCT in numeracy learning is starting from the environmental setting, welcomimg children, morning activities, opening games, eating together, and core activities consisting of: the environmental footing, the footing before playing, the footing while playing and the footing after playing. Then ending with closing.